The Relationship between Teacher Interpersonal Interaction and the Biology Learning Environment in Senior High Schools - Sanusih, Dhea Khoiriyah; Zulfiani, Zulfiani (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Biology learning that focuses more on conveying material concepts results in less classroom interaction. Each teacher's interaction skills vary, thus creating a different quality of learning environment. An ideal learning environment should stimulate curiosity and encourage active student involvement. To achieve this condition, the interpersonal interaction factor of teachers is an important variable that needs to be examined. This study was conducted with the primary focus of analyzing the relationship between teacher interpersonal interaction and the biology learning environment in Senior High Schools in South Tangerang City. The research method used was a survey with correlational techniques. There were 96 students as samples from seven different schools using the Cluster area sampling technique. Data were collected through questionnaires, specifically the Questionnaire on Teacher Interaction (QTI) and